Employability and First Nations’ Peoples: Aspirations, Agency and Commitments - O'Sullivan, Sandy (Brill, 2019)
Universities are expected to produce employable graduates. In Education for Employability, experts explore critical questions in the employability agenda: Who sets the standards and expectations of employability? How do students monitor their own employability? How can universities design whole curricula and university environments that promote employability? What teaching and learning strategies facilitate the development of employability? Responsibility for developing and sustaining employability lies with a broad coalition of the individual students, the university, alumni, the professions and industry and is accomplished through the intended curriculum as well as co-curricular, extra-curricular and supra-curricular activities, events and learning opportunities. [Book Synopsis]